Tumour Viruses (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Current worldwide estimates suggest that approxiamtely 11% of all cancers are caused by viral infections. At present, there are eight viruses that have a strong association with cancer development namely, human papillomavirus, Epstein-Barr virus, Kaposi's sarcoma-associated herpes virus, human T-cell lymphotrophic virus type I, Merkel cell polyomavirus, hepatitis B and C viruses and human immunodeficiency virus. Some of these viruses and associated cancers, such as human papillomavirus and cervical cancer, are well studied and the causal link between infection and cancer development is established. However, the involvement of these known oncogenic viruses in cancer development at other body sites is not well understood and further study of these viruses continues to highlight novel mechanisms of cellular transformation. Other cancer-associated viruses are only recently discovered, such as Merkel cell polyomavirus, and further work is required to formally prove their role in cancer development. In this Special Issue, we seek to explore novel mechanisms of cellular transformation by oncogenic viruses, the role of viral infection in cancer development in understudied body sites and the potential role of novel viral pathogens in cancer development.